Renminbi devaluation, dependence structure and currency risks / Lai Wing Choong - Lai , Wing Choong (2019)
This thesis examines the dependence structure between the exchange rate (FX) returns of Renminbi (RMB) and other currencies, estimates tail risks in FX returns of selected currencies due to larger fluctuations in RMB, and models volatility in FX returns of other currencies due to shocks in RMB and its volatility. A comparison between the onshore RMB (CNY) and the offshore RMB (CNH) is made. Within this context, the impact of the CNY devaluation on 11 August 2015 is examined. We apply the Archimedean copulas to capture the presence of lower and upper tail dependence between the returns of RMB and 13 other currencies selected for analysis, and found dependencies not revealed by the linear regression analysis. The extreme movements in RMB after the CNY devaluation have resulted in higher dependence between the returns of RMB and the selected currencies, while the market responses to large losses and gains have become more symmetrical. Subsequently, the linear and copula quantile regression are used to estimate tail risks in FX returns due to larger RMB fluctuations. Higher tail risks are found using the copula quantile regression, as financial data are usually non-linear and non-normally distributed, especially in the tails. Standard regression methods tend to under estimate tail dependence, especially when extreme event occurs. We apply the Gumbel copulas to capture the upper tail dependence between the volatility of returns in RMB and the other currencies, and found dependencies not discovered by standard ARCH models. The tail dependence between both onshore CNY and offshore CNH with the volatility in most other FX returns have increased after the CNY devaluation, and this is most obvious in the case of Asian and ASEAN-5 currencies.